Developing My Mathematics Identity. (1st October 2016) - Gonzalez, Lidia
Abstract: Assuming the role of storyteller, the author uses her experiences as a graduate student and beginning teacher to reflect critically on issues related to mathematics, mathematics education, gender, and diversity .